Optimal Design for Frequency Fluctuation Control System with SMES Unit - Xuan Khoa Tran; Y. Chen; Gia Tri Phan; D. H. Huynh (My University, 2020)
Optimal Design for Frequency Fluctuation Control System with SMES Unit
Keywords: SMES unit; Frequency fluctuation; Optimal design